The Relationship Between Lifestyle and Stress Levels in Patients with Hypertension - Intan Mawarizki Tambunan; Nurwijaya Fitri (Genius Journal, 2026)
Objective: Hypertension is a condition of increased systolic blood pressure ≥140 mmHg and diastolic ≥90 mmHg which is one of the highest causes of death in the world. This condition is influenced by various factors, especially lifestyle and stres levels. This research aims to analyze the relationship between lifestyle and stres levels in hypertensive patients in the work area of the Gerunggang Health Center in 2025. Method: This research uses a quantitative method with a correlational design and a cross-sectional approach. The research population is all hypertension patients who visited the Pangkalpinang City Gerunggang Health Center for treatment in July 2025 as many as 260 people, with a sample of 80 respondents taken using the simple random sampling technique. Research instruments in the form of lifestyle questionnaires and DASS. Data analysis is done using chi-square test and Pearson correlation test. Result: The research results show that the respondents who have a bad lifestyle as many as 60 (75.0%) and 20 (25.0%) have a good lifestyle, with a p-value of 0.031, the stres level obtained a pearson correlation p-value (0.005). Because p-value < α (0.05), it can be concluded that there is a significant relationship between lifestyle and stres level with the incidence of hypertension at the Gerunggang Health Center of Pangkalpinang City in 2025. Conclusion: The conclusion shows that there is a significant relationship between lifestyle and stres levels with the incidence of hypertension. Poor lifestyle and high stres increase the risk of hypertension, so it is necessary to educate a healthy lifestyle, stres management and routine blood pressure checks for prevention